The accuracy of rectal diagnosis of corpora lutea in water buffalo (Bubalus bubalis) - Sharifuddin, W.; Jainudeen, M.R. (Elsevier, 1983)
The accuracy of rectal diagnosis of corpora lutea (CL) was determined by direct inspection of the ovaries by laparoscopy in 68 suckled water buffalo (Bubalus bubalis). Thirty-eight (81%) of the 47 CL diagnosed by rectal palpation were confirmed at laparoscopy. Errors in rectal diagnosis of CL were due to failure to palpate early CL (8.5%) and to follicles (> 10 mm in diameter) raised above the ovarian surface (10.6%) being diagnosed as CL. Twenty-six (89.7%) of the 29 diagnoses of luteal tissue by the progesterone assay were confirmed. Errors were due to the presence of CL with low progesterone (10.3%). The overall accuracy of diagnosing a follicle or a CL by rectal palpation and plasma progesterone assay was 81 and 86% respectively. The study indicated that rectal palpation is as reliable as the progesterone assay for the diagnosis of CL in the buffalo.